Pablo de Olavide y la nueva planta de los estudios - Liendo Tagle, Fernando (Historia de las Universidades, 2016)
In the context of the reforms during the reign of Charles III of Spain, the figure of Pablo de Olavide y Jáuregui (1725-1803) is particularly noteworthy not only due to his literary achievements, his famous trial and condemnation by the Inquisition, but also for his legacy in the area of government. His efforts to overhaul university structures, teaching practices and curricula -particularly in the field of Law- were amongst his key initiatives. These reforms were contained in a new teaching programme that Olavide conceived for the University of Seville, which was articulated in a report commissioned by Charles III in 1768. The book contains a brief profile of Pablo de Olavide and a chronicle of the origin and development of university reform. Transcriptions of unpublished primary sources as manuscripts, letters and reports from various archives are included.---Estudio sobre el intento de reforma ilustrada de la Universidad de Sevilla en 1768, conducida por Pablo de Olavide y Jáuregui (1725-1803). Contiene una breve semblanza de Olavide, así como una crónica sobre la gestación y desarrollo de la reforma, de la que formó parte un amplio informe donde se sintetizaron estos planteamientos nuevos. Se incluyen transcripciones de los documentos fundamentales de la reforma que el Consejo de Castilla encargó a Olavide como Asistente de la ciudad de Sevilla, en lo tocante a las enseñanzas superiores.